Transport theory for femtosecond laser-induced spin-transfer torques. (22nd February 2018) - Baláž, Pavel; Žonda, Martin; Carva, Karel; Maldonado, Pablo; Oppeneer, Peter M
Abstract: Ultrafast demagnetization of magnetic layers pumped by a femtosecond laser pulse is accompanied by a nonthermal spin-polarized current of hot electrons. These spin currents are studied here theoretically in a spin valve with noncollinear magnetizations. To this end, we introduce an extended model of superdiffusive spin transport that enables the treatment of noncollinear magnetic configurations, and apply it to the perpendicular spin valve geometry. We show how spin-transfer torques arise due to this mechanism and calculate their action on the magnetization present, as well as how the latter depends on the thicknesses of the layers and other transport parameters. We demonstrate that there exists a certain optimum thickness of the out-of-plane magnetized spin-current polarizer such that the torque acting on the second magnetic layer is maximal. Moreover, we study the magnetization dynamics excited by the superdiffusive spin-transfer torque due to the flow of hot electrons employing the Landau–Lifshitz–Gilbert equation. Thereby we show that a femtosecond laser pulse applied to one magnetic layer can excite small-angle precessions of the magnetization in the second magnetic layer. We compare our calculations with recent experimental results.